Pengaruh Kualitas Layanan, Harga Dan Kepercayaan Terhadap Loyalitas Pelanggan (Pada Pelanggan Kereta Api di Stasiun Malang Kota) - Vinna Nisa’i Susanti Ningrum; Muhammad Agus Salim; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The objective of this study was to determine the extent to which quality of service, pricing, and trust impact train customer loyalty at Malang City Station. A quantitative method is used in this sort of study. This study was done at KAI customers Malang City Station on Jl. Trunojoyo (West Door) and Jl. Panglima Sudirman (East Door) Kiduldalem, Kec. Klojen, Malang City, East Java. The sampling approach utilized in this study is non-probability sampling, specifically the purposive sampling method, in which the sample obtained must meet particular criteria based on the research objectives. A questionnaire is used as the method or collection tool in this quantitative study. According to the findings of this study, (1) The level of service quality greatly influences customer loyalty, (2) Price has little impact on customer loyalty and (3) Trust influences customer loyalty. Keywords: Service Quality, Price, Trust, Customer Loyalty.